The causative relationship among energy efficiency, renewable energy consumption, and carbon dioxide emissions utilizing the VAR model: A case study of Tunisia from 1991 to 2022 - Saouli, Yakoub (The International tax journal, 2025)
This study investigates the causal relationship among energy efficiency, renewable energy consumption, and carbon dioxide emissions in Algeria from 1991 to 2022, employing the Variable Autoregressive Regression (VAR) model. The findings indicated a causal association between energy efficiency and carbon dioxide emissions, although no causal relationship exists among the other factors. Consequently, energy efficiency pertains to the mitigation or augmentation of carbon dioxide emissions, indicating that fewer natural resources are utilized to produce equivalent energy, resulting in a decrease in carbon dioxide emissions.